Comprehension benefits of visual-gestural iconicity and spatial referencing. (April 2023) - Saunders, Emily; Quinto-Pozos, David
Studies have shown that iconicity can provide a benefit to non-signers during the learning of single signs, but other aspects of signed messages that might also be beneficial have received less attention. In particular, do other features of signed languages help support comprehension of a message during the process of language learning? The following exploratory study investigates the comprehension of sentences in two signed and two spoken languages by non-signers and by American Sign Language (ASL) learners. The design allows for the examination of message comprehension, with a comparison of unknown spoken and signed languages. Details of the stimulus sentences are provided in order to contextualize features of the signing that might be providing benefits for comprehension. Included in this analysis are aspects of the sentences that are iconic and spatially deictic – some of which resemble common gestural forms of communication. The results indicate that iconicity and referential points in signed language likely assist with comprehension of sentences, even for non-signers and for a signed language that the ASL signers have not studied.